Decay of Dusty Fluid MHD Turbulence for Four-point Correlation in a Rotating System - PK, M. A. Bkar; Azad, M. A. K.; Sarker, M. S. A. (Journal of Scientific Research, 2012)
In this paper we have considered the dusty fluid MHD turbulence in a rotating system at four-point correlation. Here three and four-point correlations between fluctuating quantities have been considered and the quintuple correlations are neglected in comparison to the third and fourth order correlations. For the convention of calculation, the correlation equations are converted to the spectral form by taking their Fourier transforms. Finally, integrating the energy spectrum over all wave numbers, the energy decay of dusty fluid MHD turbulence in a rotating system for four-point correlation system is obtained. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.9996 J. Sci. Res. 5 (1), 77-90 (2013)